(3eHGMK CUhdjIs - (3cGTa GdZWGA, eMeO QVG Hf gGOj Hf YHGS cGTa GdZWGA, J (B1366(3g` (B1947(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3aGdbGFd jLYdfj CeKGd gPg GdGYJHGQGJ dFf Edi chfgG ef bHd GdeGOjGJ Ch GdfSH (B... (3GYde Cf eQLY cd af Edi eLehY TJGJ ef GdeSGFd GdhGajIs
(3BNQgG (B:s
(3BNQgG(B: (3dCfg jecf Cf jbGd Efg EPG hQO Gdfgj Yf aQO aMGhQ Ch GdeYGedI GdeTQhYI cGf XGgQG aj YOe GdeTQhYjI hEf cGf hGQOG Ydi eYGedI eSJbdI cGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs